PENGARUH MODEL PEMBELAJARAN STAD BERBANTUAN MEDIA KARTU BILANGAN TERHADAP HASIL BELAJAR OPERASI HITUNG CAMPURAN SISWA KELAS III SD NEGERI 106845 UJUNG NEGERI KAHAN - Richa Putri Br. Simanjuntak; Robenhart Tamba; Halimatussakdiah; Natalia Silalahi; Nur Hudayah (STKIP Subang, 2026)
This study aimed to determine the effect of the Student Teams Achievement Division (STAD) learning model assisted by number card media on the learning outcomes of mixed arithmetic operations among third-grade students at SD Negeri 106845 Ujung Negeri Kahan and to determine the improvement in students’ learning outcomes after the implementation of the model. This research employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest Design. The sample consisted of 21 third-grade students. Data were collected through a learning achievement test and analyzed using the normality test, Paired Sample t-test, and N-Gain test with SPSS. The results showed that the implementation of the STAD learning model assisted by number card media had a significant effect on students’ learning outcomes, with a significance value (Sig. 2-tailed) of 0.000 < 0.05. The mean score increased from 45.48 on the pretest to 80.81 on the posttest, while the N-Gain result was in the moderate category. Therefore, it can be concluded that the STAD learning model assisted by number card media has a significant effect and is effective in improving students’ learning outcomes in mixed arithmetic operations.